The evaluation of a 2D diode array in "magic phantom" for use in high dose rate brachytherapy pretreatment quality assurance. Issue 2 (12th January 2015) - Espinoza, A.; Petasecca, M.; Fuduli, I.; Howie, A.; Bucci, J.; Corde, S.; Jackson, M.; Lerch, M. L. F.; Rosenfeld, A. B.
Abstract : Purpose: High dose rate (HDR) brachytherapy is a treatment method that is used increasingly worldwide. The development of a sound quality assurance program for the verification of treatment deliveries can be challenging due to the high source activity utilized and the need for precise measurements of dwell positions and times. This paper describes the application of a novel phantom, based on a 2D 11 × 11 diode array detection system, named "magic phantom" (MPh), to accurately measure plan dwell positions and times, compare them directly to the treatment plan, determine errors in treatment delivery, and calculate absorbed dose. Methods: The magic phantom system was CT scanned and a 20 catheter plan was generated to simulate a nonspecific treatment scenario. This plan was delivered to the MPh and, using a custom developed software suite, the dwell positions and times were measured and compared to the plan. The original plan was also modified, with changes not disclosed to the primary authors, and measured again using the device and software to determine the modifications. A new metric, the "position–time gamma index, " was developed to quantify the quality of a treatment delivery when compared to the treatment plan. The MPh was evaluated to determine the minimum measurable dwell time and step size. The incorporation of the TG‐43U1 formalism directly into the software allows for dose calculations to be made based on the measured plan. The estimated dose distributions calculated by the software were compared to the treatment plan and to calibrated EBT3 film, using the 2D gamma analysis method. Results: For the original plan, the magic phantom system was capable of measuring all dwell points and dwell times and the majority were found to be within 0.93 mm and 0.25 s, respectively, from the plan. By measuring the altered plan and comparing it to the unmodified treatment plan, the use of the position–time gamma index showed that all modifications made could be readily detected. The MPh was able to measure dwell times down to 0.067 ± 0.001 s and planned dwell positions separated by 1 mm. The dose calculation carried out by the MPh software was found to be in agreement with values calculated by the treatment planning system within 0.75%. Using the 2D gamma index, the dose map of the MPh plane and measured EBT3 were found to have a pass rate of over 95% when compared to the original plan. Conclusions: The application of this magic phantom quality assurance system to HDR brachytherapy has demonstrated promising ability to perform the verification of treatment plans, based upon the measured dwell positions and times. The introduction of the quantitative position–time gamma index allows for direct comparison of measured parameters against the plan and could be used prior to patient treatment to ensure accurate delivery.